THE HISTORY OF INDONESIAN LEGISLATION IN ESTABLISHING A JUST NATIONAL LEGAL SYSTEM - Priya Pratama; Andrey Nasrullah Kamal; Ahmad Sarwad; Masyuri Said Shahdan; Bunrafiq; M Jibran Faiz; A. Faisal Mahendra; Desmarani Helfisar (International Journal of Multidisciplinary Reseach, 2026)
This study examines the historical development of Indonesian legislation and its contribution to establishing a just national legal system. Using a qualitative approach with normative legal research, the study analyzes constitutional provisions, statutory regulations, legal doctrines, and relevant scholarly literature. The findings indicate that Indonesian legislation has evolved through several historical periods, from customary and colonial legal systems to the contemporary legislative framework based on Pancasila and the 1945 Constitution. Legislative reforms, particularly during the Reform Era, have strengthened legal certainty, democratic governance, and public participation. Nevertheless, challenges such as regulatory overlap and legislative inconsistencies remain. Continuous legislative reform is therefore essential to promote justice, legal certainty, and sustainable national legal development.